Study of Anti-psoriatic activity and Evaluation of E2A Gene Expression for Psoriasis Levels by RT-PCR of Thespesia populnea L. Methanolic Leaf Extract - Narendar Vankudothu; Chandrashekhar R; Sudhakar Chekuri; Lakshmi Bhavani N; Anwar SY (International Journal of Life Sciences, 2018)
Thespesia populnea L. (Malvaceae) traditionally claimed to be constructive in the cure of cutaneous infections such as scabies, psoriasis, ringworm, guinea worm, eczema and herpetic diseases. Oil prepared by boiling the ground bark and leaves in coconut oil is applied externally in psoriasis and scabies. Conversely there are no customary scientific reports for its anti-psoriatic activity. Hence the plant Thespesia populnea has been chosen to establish scientific data for its traditional claim as anti-psoriatic. In the present study a chemical test performed against all the phytochemical constituents for their preliminary screening of each solvent extract of leaf like water, methanol, chloroform, ethyl acetate, pet ether and acetone. From the phytochemical analysis of the leaf extracts; the result infers the presence of glycosides, tannins, flavonoids, triterpenoids and phytosterols in all the solvent extracts. But phenols are more retained in methanolic leaf extract compared to all the phytochemical constituents. Screening for anti-psoriatic activity was carried out by topical application of methanolic leaf extract of Thespesia populnea in the form of a cream using the Perry’s scientific mouse tail model. Successive methanolic leaf extract showed paramount anti-psoriatic activity than the standard drug Retion-A (0.05%). Potential function of E2A as a biomarker in psoriasis, is applied in the current investigation to study whether the methanolic leaf extracts of Thespesia populnea L. showed antipsoriatic effect targeting E2A gene expression for the psoriasis levels. Results indicated that methanolic leaf extract of Thespesia populnea can preferably be used as anti-psoriatic drug and the plant is promising for further investigations to prove its anti-psoriatic activity with no side effects.